Undertaking Community Engagement for a Controlled Human Malaria Infection Study in Kenya: Approaches and Lessons Learnt - Mumba, Noni; Njuguna, Patricia; Chi, Primus; Marsh, Vicki; Awuor, Esther; Hamaluba, Mainga; Mauncho, Cynthia; Mwalukore, Salim; Masha, Johnson; Mwangoma, Mary; Kalama, Betty; Alphan, Hassan; et al. (Frontiers in Public Health, 2022)
Human Infection Studies (HIS) involve deliberately infecting healthy volunteers with disease causing pathogens under controlled conditions. These studies are ‘controlled’ by way of the specificity in terms of type of pathogen being used, including dose, and availability of emergency medical facilities to research volunteers. Most HIS involve diseases whose treatment is known and are done to accelerate the development of novel therapeutics such as vaccines, to address emerging and existing infectious diseases. Traditionally, HIS have been conducted primarily in high income countries (HICs), but in the recent past they are increasingly being conducted in Low-and-Middle Income Countries (LMICs). However, HIS are likely to raise concerns amongst various stakeholders including participating populations, regulatory bodies, that are unfamiliar with this type of research. The idea of deliberately infecting a healthy individual with a disease-causing pathogen seems to go against the normal practice of medicine of “do no harm”. Such types of studies can give rise to increased rumours and jeopardize research participation in study activities, including non-HIS research. Community engagement can be one approach to address particular issues that HIS studies raise through meaningfully engaging with communities, where views and voices inform the conduct of HIS studies. Additionally, engagement can inform the ethical conduct and acceptability of HIS studies in LMIC settings and provide opportunities for sharing information, listening to, and responding to concerns and views from potential participants, and the larger community in which the study would be conducted. Despite community engagement being an important aspect to consider, very few published and grey literature cover the types of approaches that have been used, and lessons learnt in engagement for HIS. This paper outlines the community engagement approaches that were used to engage stakeholders and communities for a malaria HIS - controlled human malaria infection (CHMI), undertaken in Kilifi, Kenya. It outlines the engagement activities across the research cycle, from activities conducted during protocol development, to planning, and implementation of the study. We discuss the challenges experienced, lessons learnt, and provide some recommendations for engagement around HIS.